A Highly Efficient Composite Catalyst Constructed From NH2-MIL-125(Ti) and Reduced Graphene Oxide for CO2 Photoreduction - Zhao, Yunxia; Cai, Wei; Chen, Jiaxin; Miao, Yuanyuan; Bu, Yunfei (Frontiers in Chemistry, 2019)
Substantial consumption of fossil fuels causes an increase in CO2 emissions and intensifies global pollution problems, such as the greenhouse effect. Recently, a new type of ultra-low-density porous material, metal-organic frameworks (MOFs), has been developed for the photocatalytic conversion of CO2. Herein, a composite photocatalytic catalyst based on NH2-MIL-125(Ti) and reduced graphene oxide (rGO@NH2-MIL-125) was fabricated through a facile "one-pot" process. The acquired materials were characterized to obtain their structures, morphologies and optical information. The experimental results showed that methyl formate (MF) was the predominant reaction product, and rGO@NH2-MIL-125 exhibited the highest yield of 1116 μmol·g-1·h-1, more than twice that of pure MIL-125. The high photoactivity of rGO@NH2-MIL-125 can be ascribed to the eﬀective spatial separation and transfer of photoinduced carriers, largely due to the synergistic effect of amino functionality and rGO incorporation. rGO@NH2-MIL-125 also displayed acceptable repeatability in cyclic runs for CO2 reduction.